Development of standardized herbal therapy of bangle extract (Zingiber Cassumunar Roxb.) on the expression of Icam - 1 for complementary therapy to prevent complications in Malaria - Utami, Wiwien Sugih; Fatmawati, Heni; Hermansyah, Bagus (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Background : Malaria is still a major problem, both in international and national scale. Erythrocytes containing Plasmodium sp. will stimulate the release of Th1 (T helper-1) and release monocytes and macrophages to perform phagocytosis and produce tumor necrosis factor-alpha (TNF-α). The release of iNOS and free radicals would increase the expression of adhesion molecules such as ICAM-1, VCAM-1, CD36, and P-selectin. Research shows that IL- 10 can inhibit the production of TNF - α and IL - 1. TNF-α and ICAM - 1 play a role in the occurrence of cerebral malaria. Bangle (Zingiber cassumunar Roxb.) has a lot of potentials to be utilized as a complementary therapy to prevent the complications of malaria. Objective : This study aims to find the ability of Bangle (Zingiber cassumunar Roxb.) extract as an immunostimulant which would be used as a complementary therapy for standard malaria treatment. Methods : A number of 25 mice Balb/C males were divided into 5 groups, stimulated with methanol fractions of Bangle extract for 14 consecutive days before infected with Plasmodium berghei. All groups were examined for parasite daily, until day 7 post-positive malaria, referring to Artemisinindose regimen administered orally 0.04 mg/g bw/day for 7 days. Results : This study proves that the administration of Artemisinin combined with methanol fraction of Bangle extract provides better results to inhibit ICAM-1 gene expression in malaria-infected mice compared to single-therapy Artemisinin or methanol fraction of bangle extract. Conclusion : The combination of artemisinin and methanol fraction of Bangle extract can inhibit ICAM-1 gene expression in malaria-infected mice better compared to without the combination.